PENGEMBANGAN MEDIA PEMBELAJARAN SPESIMEN INVERTEBRATA DAN VERTEBRATA UNTUK MATERI DUNIA HEWAN KELAS X SMA NEGERI 1 RAMBAH - Mayana, Sri (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2016)
This study was conducted to investigate the properness of learning media by using specimen ofinvertebrate and vertebrate in topic of animals world at ten grade of Senior High School based onthe result of validation by the expert team and the students responses. This study was conducted inMarch to December 2015. This study used a developing research (Research & Development)based on Dick and Carey model which modified. Data collection was conducted by providingquestionnaires and in analyzing the data by descriptive analysis. The results of this research showsthat the learning media by using specimen of invertebrate and vertebrate in topic of animals worldat teen grade of Senior High School is very good criteria, based on validation of contents experts(92.50%), validation of media experts (82.99%), the individual (89.58%), small group (89.17%)and a field (89.30%) the result is very good criteria.